MASALAH GIZI DAN PERAN GIZI SEIMBANG - Laswati, Dyah Titin (Universitas Widya Mataram, 2017)
Good nutrition will be consistent with good health. In the clinical symptoms of malnutrition is the body's growth and not normal development. Nutritional status was the final result of the various factors that may relate to one anothers. Therefore, understanding how the nutrient problems should be the basis for a strategy for the prevention and mitigation. The nutritional status is directly influenced by two things, the adequacy of nutrient intake to meet the needs of the body and the infection status of a person, mutually influential, so fixing one of them is not going to fix the state of the other. The guidelines of balanced nutrition was the best solution in Indonesia visualized in Tumpeng of balanced nutrition. Data of nutritional health status and nutrition-related non-communicable diseases of data obtained from the Health Research by the Ministry of Health, 2010 and micronutrient status data, especially iron deficiency anemia status. The agreement of the World Food Conference in Rome in 1992 set of recommendations to all countries, particularly developing countries to replace the slogan-based